A longitudinal study to COVID-19 infection among university students: Physical fitness changes and psychological responses - Yuning Hao; Jay Lee; Water Soi Po Wong; Frankie U. Kei Wong; Walter Heung Chin Hui; Gasper Chi Hong Leong; Zhaowei Kong (Journal of Exercise Science & Fitness)
Background: The impact of COVID-19 infection on physical and mental health of young adults remains unclear. This study aimed to investigate the changes in the physical fitness three months after recovering from acute COVID-19 infection, and examine if the infection could also influence the mental health of university students. Methods: A total of 460 university students (mean age 18.9 ± 1.3 years, with 30 males and 27 females uninfected with COVID-19) volunteered for the study. Participants underwent a fitness test initially, followed by another physical fitness test and a mental health assessment three months after the infection of COVID-19. Physical fitness tests included body composition, flexibility, cardiorespiratory fitness, muscle strength, and muscular endurance. Mental health was assessed using the Depression-Anxiety-Stress Self-Assessment Scale (DASS-21), the Pittsburgh Sleep Quality Inventory (PSQI), and the Post-Traumatic Stress Disorder Self-Assessment Scale (PTSD). Results: Three months after acute COVID-19 infection, the physical performance of university students had decreased compared to pre-infection levels by approximate 3–15 % (p < 0.05). Regarding mental health, a notable difference was observed in sleep quality, with the positive group scoring 19 % higher than the negative group (p < .05, d = .44). Sex (β = .164, p < .05), previous infection (β = .277, p = .019) and anxiety (β = .373, p = .002) were predictive of PSQI scores, accounting for 37.5 % of the variance. Conclusions: All participants experienced a decline in physical fitness compared to their pre-infection levels, regardless of infection status. Those who had been infected exhibited poorer sleep quality compared to their non-infected peers. Prior COVID-19 infection and higher anxiety levels may contribute to poorer sleep quality.